(untitled) (Shaheed Smriti Journal, 2024)
This study examines the socio-cultural changes within the Tharu community in Khairahani Municipality, Ward No. 12, Chitwan. The research is based on interviews with key informants, participant observation, and secondary data analysis from various sources. Socio-cultural assimilation occurs when two different cultural groups coexist, with the more dominant culture eventually influencing the local one. The study highlights the significant impact of the migrant hill populations on Tharu culture, particularly through modernization and urbanization. The research identifies dramatic shifts in cultural practices, especially in life cycle rituals such as birth, naming ceremonies, marriage, death, and festivals. These changes, driven by both internal and external factors, are explored in-depth, reflecting the evolution of Tharu culture from past traditions to present-day practices. Data collected from focused group discussions and interviews with key informants provide rich insights into these transformations within the community.